Analysis and Design of Information System for Parking Management â€œParkHereâ€ Using Design Thinking Method - Richard Emmanuel Adrian Sinaga; Jonathan Tristan Santoso; Irene Sonbay; Aloisius Gita Nathaniel; Faskalis Halomoan Lichkman Manurung; Yerik Afrianto Singgalen (Journal of Information System and Informatics, 2023)
Finding a secure and comfortable parking space is one of the needs of automobile owners when they visit retail centers. The ability of parking lot managers to provide information on sufficient capacity and access presents a barrier to delivering parking facilities in retail centers. Due to this, a website-based parking facility management information system is required, allowing drivers to make reservations and payments online based on when they plan to visit the shopping center. The method used in the design of ParkHere information systems is design thinking which consists of empathizing, defining, ideating, prototyping, and testing stages. The output of this study shows that at the empathize stage, motorists need information about the capacity of parking lots in various shopping centers before visiting the location. At the defined stage, this shows the need for motorists for website-based and real-time parking facility information. At the idea stage, it is necessary to design an information system based on the website that provides information on the capacity of parking facilities based on the operational time of the shopping center. At the prototype and testing stages, the ParkHere information system can answer the user's needs in choosing a place and location for vehicle parking based on the specified time.